NEW DISCOVERIES ON THE FINITE p-GROUPS OF ORDER 2(n+6) (2020)
The finite nilpotent groups can now be formed in various dimension. As such, results up to two dimensions are now obtainable. In this paper, the fuzzy subgroups of the nilpotent product of two abelian subgroups of orders n2 and 64. Here, the integers n > 6 have been successfully considered and the derivation for the explicit formulae for its number distinct fuzzy subgroups were calculated.